2022
DOI: 10.1021/acs.organomet.1c00711
|View full text |Cite
|
Sign up to set email alerts
|

Titanocene Lewis Acid Complexes with Diversified N,O-Ligands: Selectivity toward Three-Component Friedel–Crafts Reactions of Indoles

Abstract: Titanocene complexes by N,O-ligands were rationally designed and tuned for selective three-component aza-Friedel–Crafts reactions of indoles, aldehydes, and unmodified aniline. The combination of Cp2TiCl2 and 8-hydroxyquinoline favored the synthesis of the mono aza-Friedel–Crafts adducts, whereas Cp2TiCl2 combined with anthranilic acid overwhelmingly formed bis-indoles. 1H NMR titration experiments, mass spectroscopy, X-ray crystal structure analyses, and control experiments showed that the reaction of Cp2TiCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Since then, various alternative acids have been applied including protic acids, such as silica-bonded S-sulfonic acid [ 13 ], polyvinylsulfonic acid (PVSA) [ 14 ], kaolin-supported H 2 SO 4 [ 15 ], polyvinylpolypyrrolidone-supported triflic acid (PVPP . OTf) [ 16 ], ascorbic acid [ 17 ], phosphoric acid [ 18 ], benzenesulfonic acid [ 19 ], chitosan–SO 3 H (CTSA) [ 20 ], phthalimide- N -sulfonic acid (PISA) [ 21 ] and SiO 2 -KHSO 4 [ 22 ] as well as Lewis acids, such as FeCl 3 [ 23 24 ], RuCl 3 ·3H 2 O [ 25 ], AgNO 3 [ 26 ], glycerol and [Fe(III)-(salen)]Cl [ 27 ], Fe(DS) 3 · n H 2 O [ 28 ], Sc(OTf) 3 [ 29 ], B(C 6 F 5 ) 3 or PhSiCl 3 [ 30 ] and Cp 2 TiCl 2 [ 31 ]. However, most of these reactions face some serious drawbacks, such as the requirement of large quantities of the catalyst due to present moisture or formation of adducts with the substrate, long reaction times, lower yields, and production of large amounts of toxic waste during work-up.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, various alternative acids have been applied including protic acids, such as silica-bonded S-sulfonic acid [ 13 ], polyvinylsulfonic acid (PVSA) [ 14 ], kaolin-supported H 2 SO 4 [ 15 ], polyvinylpolypyrrolidone-supported triflic acid (PVPP . OTf) [ 16 ], ascorbic acid [ 17 ], phosphoric acid [ 18 ], benzenesulfonic acid [ 19 ], chitosan–SO 3 H (CTSA) [ 20 ], phthalimide- N -sulfonic acid (PISA) [ 21 ] and SiO 2 -KHSO 4 [ 22 ] as well as Lewis acids, such as FeCl 3 [ 23 24 ], RuCl 3 ·3H 2 O [ 25 ], AgNO 3 [ 26 ], glycerol and [Fe(III)-(salen)]Cl [ 27 ], Fe(DS) 3 · n H 2 O [ 28 ], Sc(OTf) 3 [ 29 ], B(C 6 F 5 ) 3 or PhSiCl 3 [ 30 ] and Cp 2 TiCl 2 [ 31 ]. However, most of these reactions face some serious drawbacks, such as the requirement of large quantities of the catalyst due to present moisture or formation of adducts with the substrate, long reaction times, lower yields, and production of large amounts of toxic waste during work-up.…”
Section: Reviewmentioning
confidence: 99%
“…[99]. After repeated studies and experiments on the reaction between indole (11) and benzaldehyde (31), methanol emerged as the optimum solvent with the isolated product yield approaching 98%, after 1 hour, when 69 mg of the nanocomposite were added to the reaction mixture [99]. The recovery of the nanocatalyst was feasible by simple filtration and it was found that its catalytic efficiency would not diminish even after 3 cycles [99].…”
Section: Nanocatalysismentioning
confidence: 99%